PENGARUH KESADARAN MEREK(BRAND AWARENESS), KUALITAS PRODUK (PRODUCT QUALITY), DAN LOKASI (LOCATION) TERHADAP KEPUTUSAN PEMBELIAN (TO BUYING DECISIONS) PADA PERUMAHAN PURI REVENO ASRI MEDAN - Dheargo Tamba Ginting; Henri Saragih; Selamat Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the influence of brand awareness, product quality, and location on purchasing decisions at the Puri Reveno Asri Medan housing complex. The research method used is a quantitative approach with a descriptive research design. The population consists of 76 residents of the Puri Reveno Asri Medan housing complex in 2024–2025. The sampling technique employed is a census method, where all members of the population are included as research samples. The results show that partially, brand awareness has a positive and significant effect on purchasing decisions with a t-value of 3.708 > t-table 1.993 and a significance level of 0.000 < 0.05. Product quality also has a positive and significant effect with a t-value of 4.556 > t-table 1.993 and a significance level of 0.000 < 0.05. Location has a positive and significant effect with a t-value of 4.089 > t-table 1.993 and a significance level of 0.000 < 0.05.Simultaneously, brand awareness, product quality, and location have a positive and significant effect on purchasing decisions with an F-value of 50.091 > F-table 2.73 and a significance level of 0.000 < 0.05. The adjusted R-square value of 0.663 indicates that 66.3% of the variation in purchasing decisions can be explained by these three variables, while the remaining 33.7% is influenced by other variables not examined in this study.